At the NATO Summit in Chicago. A smart meeting - Priego, Alberto (Razón y fe, 2018)
The recent NATO summit, taken place in Chicago, won’t go down in history because of the new commitments that were signed. It has expressed concern once again about what the future of Afghanistan and Pakistan means for the NATO; bearing in mind budgetary and military issues, which the good or the bad situation of this institute of faith will depend on.